2014
DOI: 10.1002/mc.22201
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of 5‐hydroxymethylcytosine in rat liver with subchronic exposure to genotoxic carcinogens riddelliine and aristolochic acid

Abstract: The level of 5-hydroxymethylcytosine (5-hmC) converted by ten-eleven translocation (TET) family is decreased in cancers. However, whether 5-hmC level is perturbed in early stages of carcinogenesis caused by genotoxic carcinogens is not defined. 5-hmC levels and TET2 expression were measured in liver of rats treated with genotoxic carcinogens, riddelliine, or aristolochic acid. Levels of 5-hmC and TET2 expression decreased in the liver of the carcinogens-treated rats. Loss of 5-hmC correlates well with document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…DNA methylation reprogramming has been previously noted for a host of tumour types including HCC (2,14,16,37). In addition, changes to the normal 5hmC patterns have also been reported in both mouse and rat livers following exposure to either non-genotoxic or genotoxic agents (13,19,38). In this present study we build on these early observations to show for the first time in mouse models of liver cancer that early perturbations in the epigenetic landscape over transcriptionally silent CGIs that are marked by low levels of 5hmC and H3K27me3.predicate hyper-methylation that occurs in tumours.…”
Section: Discussionmentioning
confidence: 94%
“…DNA methylation reprogramming has been previously noted for a host of tumour types including HCC (2,14,16,37). In addition, changes to the normal 5hmC patterns have also been reported in both mouse and rat livers following exposure to either non-genotoxic or genotoxic agents (13,19,38). In this present study we build on these early observations to show for the first time in mouse models of liver cancer that early perturbations in the epigenetic landscape over transcriptionally silent CGIs that are marked by low levels of 5hmC and H3K27me3.predicate hyper-methylation that occurs in tumours.…”
Section: Discussionmentioning
confidence: 94%
“…The reduced 5hmC level in the Mdr2-KO liver may reflect, in part, the reduced active demethylation of multiple CpG sites; the total number of such sites in the genome could be significantly higher than the number of the specific CGIs detected in our study. The level of 5hmC in the liver is known to be decreased in cancer and at the pre-cancerous stage [ 35 ], including human liver cancer [ 36 ] and chemically induced hepatocarcinogenesis in mice [ 37 ], as well as in rodent liver subjected to chronic [ 38 ] or sub-chronic [ 39 ] genotoxic treatments. We are not aware of studies exploring the 5hmC dynamics during liver regeneration; however, the recent finding of the reduced 5hmC level during regeneration of zebrafish fin [ 40 ] supports the negative correlation between cell proliferation and 5hmC level.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that in the mouse liver that promoter 5hmC patterns can reflect both acute and chronic exposure to carcinogenic agents in a model of nongenotoxic carcinogenesis [84][85][86]. In addition, a global decrease in the level of 5hmC was noted following subchronic exposures to the genotoxic carcinogens riddelliine and aristolochic acid in rat liver [87]. Thus, 5hmC can be regarded as an 'identifier of cell type or disease state,' with specific 5hmC patterns dependant on the length of time of exposure to a carcinogenic agent.…”
Section: Hmc 'Barcoding' To Identify Carcinogenic Compoundsmentioning
confidence: 95%